Electrochemical determination of tetrabromobisphenol A in water samples based on a carbon nanotubes@zeolitic imidazole framework-67 modified electrode. Issue 4 (10th January 2020) - Zhou, Tingting; Zhao, Xiaoya; Xu, Yinghua; Tao, Yun; Luo, Dan; Hu, Liqin; Jing, Tao; Zhou, Yikai; Wang, Peng; Mei, Surong
Abstract : Carbon nanotubes@zeolitic imidazole framework-67 (CNTs@ZIF-67), a conductive composite was prepared from carboxylic carbon nanotubes and a cobalt–imidazole framework. Abstract : Carbon nanotubes@zeolitic imidazole framework-67 (CNTs@ZIF-67), a conductive composite was prepared from carboxylic carbon nanotubes and a cobalt–imidazole framework. It possesses an excellent adsorption capacity (92.12 mg g −1 ) for the flame retardant tetrabromobisphenol A (TBBPA). The composite was characterized by transmission and scanning electron microscopy, FTIR and X-ray diffractometry. It was then used to modify an acetylene black electrode. Electrochemical studies showed the current response of the modified electrode to be larger than that of electrodes modified with CNTs-COOH or ZIF-67 only. Electrochemical impedance spectroscopy showed this material combination to improve the conductivity of ZIF-67. The addition of perfluorodecanoic acid further improves the response. The sensor is stable, reproducible, and has a linear range of 0.01–1.5 μM TBBPA concentration, with a 4.2 nM detection limit (at S/N = 3). The sensor was successfully applied to the detection of TBBPA in spiked rain and pool water samples.